2017
DOI: 10.1159/000454915
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Autologous Platelet-Rich Plasma on Bone Regeneration by Autologous Mesenchymal Stem Cells Loaded onto Allogeneic Cancellous Bone Granules

Abstract: To develop a clinically effective bone regeneration strategy, we compared bone regeneration using allogeneic cancellous bone granule scaffolds loaded with autologous bone marrow-derived mesenchymal stem cells (BM-MSC) with or without autologous platelet-rich plasma (PRP). Critical-sized segmental bone defects were made at the mid-shaft of both radiuses in 41 New Zealand White rabbits. Small-sized allogeneic cancellous bone granules (300-700 μm in diameter) loaded with BM-MSC were implanted on one side, and PRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…The main issue with lack of standardization is exemplified by one study which found that PRP had no significant effect on bone healing, however, a closer look at the platelet numbers used in the study found that some of the PRP tested had over 16‐fold more platelets than other PRP. Despite the vast differences in platelet numbers and omitted leukocyte numbers, these products were all classified under the same umbrella term “PRP.” This is commonplace across the literature, whereby, the absence of standardized nomenclature, quality control, as well as thorough analysis of cellular contents, makes it difficult to draw clear conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…The main issue with lack of standardization is exemplified by one study which found that PRP had no significant effect on bone healing, however, a closer look at the platelet numbers used in the study found that some of the PRP tested had over 16‐fold more platelets than other PRP. Despite the vast differences in platelet numbers and omitted leukocyte numbers, these products were all classified under the same umbrella term “PRP.” This is commonplace across the literature, whereby, the absence of standardized nomenclature, quality control, as well as thorough analysis of cellular contents, makes it difficult to draw clear conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a most recent research by Joo et al () has compared bone regeneration using allogeneic cancellous bone granule scaffolds loaded with autologous bone marrow‐derived mesenchymal stem cells (BM‐MSC) with or without autologous platelet‐rich plasma (PRP), and showed a similar progression of new bone formation and maturation. Furthermore, several recent reports have highlighted the advantages of adipose‐derived stem cells (ASCs) over other stem cells that are derived from bone marrow.…”
Section: Introductionmentioning
confidence: 99%
“…Platelet is highly specialized secretory cell release growth factors with cytokines to improve healing process (8). These platelet growth factors enhance chemotaxis, induction, differentiation and proliferation of progenitor osteoblasts and influences on bone cells activity (9).…”
mentioning
confidence: 99%